2015
DOI: 10.1007/s00103-015-2271-x
|View full text |Cite
|
Sign up to set email alerts
|

Gewalt gegen Kinder

Abstract: Violence against children is a widespread phenomenon. Interpersonal violence within the family context is typical in childhood, whereas violence occurs more frequently in the leisure and peer context during adolescence, often involving new media. The risk for experiencing violence is associated with many different factors, for example the age, psychosocial context, and cultural background of a child. Data on the prevalence of violence vary by country, depending on the available documentation systems. It is est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
4
0
1
Order By: Relevance
“…The risk of experiencing violence is associated with many important factors, for example, the child’s age, psychosocial context, and cultural background [ 1 ]. Violence risk factors can be divided into modifiable and unmodifiable.…”
Section: Violence In Cultural Termsmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of experiencing violence is associated with many important factors, for example, the child’s age, psychosocial context, and cultural background [ 1 ]. Violence risk factors can be divided into modifiable and unmodifiable.…”
Section: Violence In Cultural Termsmentioning
confidence: 99%
“…Violence against children is a widespread phenomenon. The family remains the most common source of violence in the early years of human life [ 1 ].Childhood is a critical period during which one’s personality is formed [ 2 ]. Those who do not grow up with healthy relationship models during childhood have difficulty building relationships in the future [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…70% in unterschiedlichen Studien (17,21). Aber auch wenn Kinder nicht selbst körperlich misshandelt werden und "nur" Zeuge der Misshandlung der Mutter sind, lässt sich dies als eine Form von emotionaler/psychischer Misshandlung des Kindes interpretieren (17,23,24), die langfristige Auswirkungen auf dessen weitere Entwicklung haben kann.…”
Section: Häusliche Gewalt Und Kinderunclassified
“…2 matic stress disorder (PTSD) symptoms, such as helplessness, flashbacks, intense fear, or nightmares. [11][12][13][14][15] Research on medical visits in US found that youth were more self-injurious and violent, more likely to use drugs, and to be referred to intensive treatment. 16 Nevertheless little is known about the incidence of treatment in a hospital by violence experience among adolescents in South Korea.…”
Section: Introductionmentioning
confidence: 99%